Politics as care of the passions in Plato: on the treatment of benevolence in the Gorgias - Gómez Pérez, Gustavo (ΠΗΓΗ/FONS, 2020)
In the Gorgias (521d), Socrates claims to be the only Athenian who practices the real art of politics in his time. The present paper interprets this assertion based on an analysis of the Greek verb θεραπεύω, which in the context of the dialogue means “serving”, “caring”, or “tending” (513e, 521a). It alludes primarily to the therapeutic character of politics by analogy with medicine, but it also can refer to the training of horses (516e). Socrates understands the practice of politics as a way of taking care of the passions, and of their relation to goodwill, which is considered to be a necessary affective disposition that is inherently political. Socratic political n practice depends on the performative possibilities of language. An irreducible tension between the political and the apolitical determines it.